Using rewards as a gamification strategy inside the english classroom (2019)
This research takes place in a private school located in Bosa, Cundinamaca called Colegio Miguel Angel Asturias. The study plan contains regular normal subjects such as, present simple, past simple, present perfect and so on. According to the principal, the school is interested in reinforcing English as second language in their students and that is why, English has five hours per week per course. There is not a pre-determined method or approach to be used in the institution regarding the teaching of the second language; they only give you the study plan and you, as teacher, are free to develop the plan as you consider the best way to do it.